2016
DOI: 10.1111/joa.12444
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarization‐activated cation and T‐type calcium ion channel expression in porcine and human renal pacemaker tissues

Abstract: Renal pacemaker activity triggers peristaltic upper urinary tract contractions that propel waste from the kidney to the bladder, a process prone to congenital defects that are the leading cause of pediatric kidney failure. Recently, studies have discovered that hyperpolarization-activated cation (HCN) and T-type calcium (TTC) channel conductances underlie murine renal pacemaker activity, setting the origin and frequency and coordinating upper urinary tract peristalsis. Here, we determined whether this ion chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 91 publications
(203 reference statements)
2
14
0
Order By: Relevance
“…GTs was also previously reported to exert analgesic actions [11,53], which could be possibly associated with its inhibition of I h in different types of sensory neurons. It is also important to note that the I h was expressed either in urinary bladder, ureter and renal pacemaker tissue or in different types of tumor cells (e.g., lung carcinoma cells) [34,54,55,56,57]; at extent GTs-induced block of I h is linked to its antineoplastic actions or impairments in urine excretion remains to be imperatively evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…GTs was also previously reported to exert analgesic actions [11,53], which could be possibly associated with its inhibition of I h in different types of sensory neurons. It is also important to note that the I h was expressed either in urinary bladder, ureter and renal pacemaker tissue or in different types of tumor cells (e.g., lung carcinoma cells) [34,54,55,56,57]; at extent GTs-induced block of I h is linked to its antineoplastic actions or impairments in urine excretion remains to be imperatively evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Though HCN channels are generally studied in the heart and brain, these channels have been found to be expressed and regulate function in multiple organ systems [ 14 16 , 25 33 ]. In particular, HCN2 has been reported to have a functional role in many hormone secreting tissues, including the pancreas and pituitary[ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that hyperpolarization‐activated cyclic nucleotide‐gated‐3 (HCN3) channels are expressed in the proximal renal pelvis, and these channels are regulators of renal pelvic peristalsis in multi‐ and unicalyceal species (Hurtado et al . 2010, 2014; Hurtado & Smith, 2016). Antagonists of these channels, namely ZD7288 dysregulate pacemaker activity, leading to ineffective proximal‐to‐distal contractions (Lang, 2010; Hurtado et al .…”
Section: Resultsmentioning
confidence: 99%
“…2014). The cell type that expresses HCN3 in the renal pelvis is controversial (Feeney & Rosenblum, 2014), but a recent anatomical study suggests that ASMCs express HCN3 in multicalyceal species (Hurtado & Smith, 2016). With the same antibody used previously (Hurtado et al .…”
Section: Resultsmentioning
confidence: 99%